2018
DOI: 10.1016/j.chest.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Portable Sleep Monitoring for Diagnosing Sleep Apnea in Hospitalized Patients With Heart Failure

Abstract: Portable sleep monitoring can accurately diagnose sleep apnea in hospitalized patients with heart failure and may promote early initiation of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…There are a limited number of studies evaluating portable sleep monitor testing to diagnose OSA in patients with cardiorespiratory disorders. Recently, Aurora et al 22 examined portable sleep monitoring to diagnose sleep apnea in patients hospitalized for heart failure and concluded that sleep apnea can be accurately and efficiently identified by PM testing. Oliveira et al 2 evaluated the use of HSAT to diagnose OSA in 72 adults with COPD using the same study design as in our study, but with a different type 3 PM.…”
Section: Discussionmentioning
confidence: 99%
“…There are a limited number of studies evaluating portable sleep monitor testing to diagnose OSA in patients with cardiorespiratory disorders. Recently, Aurora et al 22 examined portable sleep monitoring to diagnose sleep apnea in patients hospitalized for heart failure and concluded that sleep apnea can be accurately and efficiently identified by PM testing. Oliveira et al 2 evaluated the use of HSAT to diagnose OSA in 72 adults with COPD using the same study design as in our study, but with a different type 3 PM.…”
Section: Discussionmentioning
confidence: 99%
“…17 In general, type III devices seem to have an acceptable reliability to identify OSA in patients with heart failure both in acute settings (in hospital) and in stable conditions (at home). 11,18,19 In our study, patients in the IHD group had preserved ejection fraction without clinical heart failure. OSA was the predominant component in patients with IHD.…”
Section: Effects Of Different Comorbiditiesmentioning
confidence: 60%
“…The AHI equivalent of other type III devices has been shown to be closer to PSG AHI if the total sleep time of PSG was used to calculate the AHI instead of the total recording time. 11 1). This can be another factor contributing to the difference between the total sleep time of PSG and the estimated total sleep time in NOX-T3 (Table 2).…”
Section: Concordance Of Nox-t3 and Psgmentioning
confidence: 99%
“…The results showed that a portable ApneaLink device could be used to identify patients with heart failure with sleep apnea (AHI≥15 and <5 events/h), which contained both obstructive and central apneas ( 58 ). In another study, researchers distinguished the central and obstructive AHI values in another study, and also found a strong correlation coefficient between HSAT and polysomnography, which indicated a possible diagnosis ( 59 ). However, HSAT does not appear to have reduced the cost, as it is only 10% lower than the cost of polysomnography for the provider ( 60 ).…”
Section: Update On Diagnosismentioning
confidence: 95%